The Protective Role of Emotional Regulation and Family Support Against Burnout in Sandwich Generation Workers - Fakhri, Syaiful; Fitriana, Yeny Famila Fasca (Nusantara Journal of Behavioral and Social Science, 2025)
Abstract. Burnout is a long-term reaction to emotional stress and stress resulting from friction between workers and their jobs. The purpose of this study was to determine the complex relationship between emotional regulation and family support with burnout problems in the sandwich generation. This study used a quantitative correlational method with burnout as the dependent variable and emotional regulation and family support as independent variables. The measurement of these variables used 3 scales, namely the Burnout scale measured by the Maslach Burnout Inventory-General Survey scale based on aspects of exhaustion, cynicism and professional efficacy. Emotional regulation was measured using the Emotion Regulation Questionnaire scale by Gross & John ERQ measuring aspects of cognitive reappraisal strategies and aspects of expressive suppression strategies. While family support was measured using a scale  adaptation and translation of the Perceived Social Support Family and Friend (PSS-Fa and PSS-Fr) scale by Procidano & Heller based on aspects of emotional support, information, and feedback. The subjects were N=120 sandwich generation workers. The results of this study are that there is a significant relationship between emotional regulation and family support with burnout in sandwich generation workers, where emotional regulation provides an effective contribution of 50.2% while family support is 41.4%.This suggests that workplace and family interventions aimed at enhancing coping strategies and support systems are critical for mitigating burnout in this sandwich generation   Abstrak. Burnout merupakan reaksi jangka panjang terhadap stres secara emosional dan stres akibat dari pergesekan antara pekerja dan pekerjaannya. Adapun tujuan penelitian ini adalah mengetahui hubungan kompleks antara regulasi emosi dan dukungan keluarga dengan masalah burnout pada generasi sandwich. Penelitian ini menggunakan metode kuantitatif korelasional dengan burnout sebagai varibel tergantung dan regulasi emosi serta dukungan keluarga sebagai variable bebas. Adapun pengukuran varibel tersebut menggunakan 3 skala yaitu skala Burnout diukur skala Maslach Burnout Inventory-General Survey berdasarkan aspek exhaustion, cynicism dan professional efficacy. Pada regulasi emosi diukur menggunakan skala Emotion Regulation Questionnaire oleh Gross & John ERQ yang mengukur aspek strategi cognitive reappraissal dan aspek strategi expressive suppression. Sedangkan dukungan keluarga diukur menggunakan skala yang diadaptasi dan translasi dari skala Perceived Social Support Family dan Friend (PSS-Fa dan PSS-Fr) oleh Procidano & Heller berdasarkan aspek dukungan emosional, informasi, dan umpan balik. Subjek merupakan pekerja generasi sandwich dengan jumlah N=120 subjek. Hasil penelitian ini adalah terdapat hubungan yang signifikan antara regulasi emosi dan dukungan keluarga dengan burnout pada pekerja generasi sandwich, dimana regulasi emosi memberikan sumbangan efektif sebesar 50,2% sedangkan dukungan keluarga sebesar 41,4%. Hal ini menunjukkan bahwa intervensi di tempat kerja dan keluarga yang bertujuan untuk meningkatkan strategi koping stress dan sistem pendukung sangat penting untuk mengurangi kelelahan pada generasi sandwich ini.